2011
DOI: 10.1002/lary.21409
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative lumbar drain placement: An independent predictor of tension pneumocephalus and intracranial complications following anterior skull base surgery

Abstract: Routine placement of perioperative lumbar drain may be associated with an increased risk of tension pneumocephalus and intracranial complications during surgery of the anterior cranial base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
0
22
1
Order By: Relevance
“…The insertion of a LD itself bears risks of its own, including mechanical failure of the device, alterations in drainage rate, surgical site or CNS infection, headaches, nausea, intracranial vessel damage, and devastating tension pneumoencephalus . Only a few studies explored potential methods (such as airway diversion, LD placement) to prevent tension pneumoencephalus and other CNS complications after skull base operations …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The insertion of a LD itself bears risks of its own, including mechanical failure of the device, alterations in drainage rate, surgical site or CNS infection, headaches, nausea, intracranial vessel damage, and devastating tension pneumoencephalus . Only a few studies explored potential methods (such as airway diversion, LD placement) to prevent tension pneumoencephalus and other CNS complications after skull base operations …”
Section: Discussionmentioning
confidence: 99%
“…The rationale for the insertion of continuous lumbar drainage is to induce dural decompression, facilitate frontal lobe manipulation, and reduce the risks of postoperative cerebrospinal fluid (CSF) leak and meningitis. However, continuous lumbar drainage itself may carry the potential risk of serious complications, such as tension pneumocephalus and meningitis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lumbar drainage has been advocated by cranial base surgeons to divert CSF to minimize the force required for frontal lobe retraction intraoperatively as well as to potentially decrease CSF leak rates postoperatively with prolonged usage by minimizing CSF egress through the defect, allowing it to heal. 2,5,6,17 However, the literature also cites numerous instances of TP complicating skull base surgery in which continuous lumbar drainage was used. 17,20 After a skull base defect is created, continuous lumbar drainage may promote the ingress of air through the skull base dural defect by creating a relatively lower pressure than the atmospheric pressure in the subarachnoid space.…”
Section: Discussionmentioning
confidence: 99%
“…Pepper et al 16 compared 2 groups of patients, in which 1 group received LD and the other group did not, and postoperative CSF leak rate was similar in both groups. 16 Further, Zhan et al 15 reported a higher complication rate in the LD group as well as an improvement in postoperative leak by conservative management with no drain in the control group and proposed that 2-10 days should be the required period for repair material to set in. We note that the best use for perioperative LD is in a highly specific subgroup of patients in whom high-flow leak is predicted and in which the patients have risk factors such as redo surgery, radiotherapy, large tumor size, or previous sinus procedures.…”
mentioning
confidence: 99%